The compliance rate for the second diagnostic evaluation after a positive fecal occult blood test: A systematic review and meta‐analysis. Issue 3 (1st April 2019) - Gingold-Belfer, Rachel; Leibovitzh, Haim; Boltin, Doron; Issa, Nidal; Tsadok Perets, Tsachi; Dickman, Ram; Niv, Yaron
Abstract : Introduction: Only a minority of patients with a positive fecal occult blood test (FOBT) undergo a follow‐up second diagnostic procedure, thus minimizing its contribution for colorectal cancer (CRC) prevention. We aimed to obtain a precise estimation of this problem and also assess the diagnostic yield of CRC and adenomas by colonoscopy in these patients. Methods: Literature searches were conducted for "compliance" OR "adherence" AND "fecal occult blood test" OR "fecal immunohistochemical test" AND "colonoscopy." Comprehensive meta‐analysis software was used. Results: The search resulted in 42 studies (512, 496 patients with positive FOBT), published through December 31, 2017. A funnel plot demonstrates a moderate publication bias. Compliance with any second procedure, colonoscopy, or combination of double‐contrast barium enema with or without sigmoidoscopy in patients with a positive FOBT was 0.725 with 95% confidence interval (CI) 0.649–0.790 ( p  = 0.000), 0.804 with 95% CI 0.740–0.856 ( p  = 0.000) and 0.197 with 95% CI 0.096–0.361 ( p  = 0.000), respectively. The diagnostic yield for CRC, advanced adenoma and simple adenoma was 0.058 with 95% CI 0.050–0.068 ( p  = 0.000), 0.242 with 95% CI 0.188–0.306 ( p  = 0.000) and 0.147 with 95% CI 0.116–0.184 ( p  < 0.001), respectively. Discussion: Compliance with diagnostic evaluation after a positive FOBT is still suboptimal. Therefore, measures to increase compliance need to be taken given the increased risk of CRC in these patients.